Wildfires. - World Book, Inc. (Chicago, Illinois World Book, 2008)
"A discussion of a major type of natural disaster, including descriptions of some of the most destructive; explanations of these phenomena, what causes them, and where they occur; and information about how to prepare for and survive these forces of nature. Features include an activity, glossary, list of resources, and index"--Provided by publisher
Includes bibliographical references (page 47) and index.
Keywords: Wildfires -- Juvenile literature